Pengaruh Perbedaan Modalitas Short Wave Diathermy (SWD) dan Transcutaneous Electrical Nerve Stimulation (TENS) terhadap Penurunan Nyeri pada Kasus Low Back Pain Myogenic - Rizqi Indika; Mianti Nurrizky Sutejo; Muhammad Dwi Kurniawan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Background: Myogenic low back pain is a common musculoskeletal disorder often triggered by repetitive or sustained incorrect body movements, leading to mild to moderate pain. Physiotherapy interventions, such as Short Wave Diathermy (SWD) and Transcutaneous Electrical Nerve Stimulation (TENS), are frequently utilized for pain management. Objective: This study aimed to investigate the comparative effectiveness of SWD and TENS in reducing pain intensity in individuals with myogenic low back pain. Method: A quasi-experimental pre-test and post-test group design was employed. Thirty-eight participants were allocated to either the SWD or TENS intervention group. The Numeric Rating Scale (NRS) was utilized to assess pain levels before and after the interventions. Results: Both SWD and TENS interventions demonstrated significant reductions in pain levels within their respective groups (p < 0.005). However, the Mann-Whitney U test revealed no statistically significant difference in pain reduction between the SWD and TENS groups (p = 0.259). 2Conclusion: While both SWD and TENS are effective in alleviating myogenic low back pain, this study found no significant difference in their efficacy.